2015
DOI: 10.3389/fnins.2015.00084
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the allatotropin precursor and receptor in the desert locust, Schistocerca gregaria

Abstract: Allatotropins (ATs) are pleiotropic neuropeptides initially isolated from the tobacco hornworm, Manduca sexta. In 2008, the first receptor for AT-like peptides (ATR) was characterized in Bombyx mori. Since then, ATRs have also been characterized in M. sexta, Tribolium castaneum, Aedes aegypti and Bombus terrestris. These receptors show sequence similarity to vertebrate orexin (ORX) receptors. When generating an EST-database of the desert locust (Schistocerca gregaria) central nervous system, we found cDNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 86 publications
2
9
0
5
Order By: Relevance
“…mori , the current study revealed the feeding regulatory function of AT by modulating intestinal contraction, which is a function, distinctive from allatoregulatory roles [32, 44]. Consistently, it is possible in other insect species that AT can modulate feeding motivation by its pleiotropic physiological and developmental functions [4547] including myoregulatory activities on the foregut [25, 26, 48], midgut [27, 49] and hindgut [50, 51].…”
Section: Discussionsupporting
confidence: 66%
“…mori , the current study revealed the feeding regulatory function of AT by modulating intestinal contraction, which is a function, distinctive from allatoregulatory roles [32, 44]. Consistently, it is possible in other insect species that AT can modulate feeding motivation by its pleiotropic physiological and developmental functions [4547] including myoregulatory activities on the foregut [25, 26, 48], midgut [27, 49] and hindgut [50, 51].…”
Section: Discussionsupporting
confidence: 66%
“…We show that SPPP-4 expression in the thorax tissue from crowded-reared individuals is higher compared to isolated-reared individuals, and SPPP-5 shows a similar but a non-significant trend, consistent with earlier studies in S. gregaria (Badisco et al, 2011;Breugelmans et al, 2008;Simonet et al, 2005). The other two target genes were allatotropin, a pleiotropic hormone that is best known as a stimulator of juvenile hormone (JH) production and a myostimulatory peptide (Kataoka et al, 1989;Lismont et al, 2015), and allatostatin, known to repress JH production in insects even though this function could not be confirmed in S. gregaria (Stay, Tobe & Bendena, 1995;Verlinden et al, 2009). We report that ast is significantly downregulated in crowded-reared locusts, and observed a similar but non-significant trend for at.…”
Section: Rna Sequencing Rt-qpcrsupporting
confidence: 89%
“…Other differences between both technique (e.g., RNA sequencing being more prone to PCR artefacts and positional bias) might play an additional role in the observed differences. An earlier study in S. gregaria reported no significant difference between isolated-reared and crowded-reared individuals for at (Lismont et al, 2015), even though the data were not shown. Together, our data might suggest differences in JH regulation between isolated-reared and crowded-reared locusts.…”
Section: Rna Sequencing Rt-qpcrmentioning
confidence: 61%
“…Mediante los alineamientos múltiples, observamos que Rp-ATr y Rp-AST-Cr comparten un alto grado de similitud con los receptores de otros insectos pertenecientes a especies de holometábolos y hemimetábolos (Vuerinckx et al, 2011;Horodyski et al, 2011;Nouzova et al, 2012;Verlinden et al, 2013;Lismont et al, 2015).…”
Section: Discussionunclassified
“…El receptor de AT (ATr) ha sido caracterizado genómica y funcionalmente por su alto grado de similitud con el receptor de orexina de vertebrados, en diferentes especies de insectos como B. mori, T. castaneum, M. sexta, A. aegypti, B. terrestres, S. gregaria (Yamanaka et al, 2008;Vuerinckx et al, 2011;Horodyski et al, 2011;Nouzova et al, 2012;Verlinden et al, 2013;Lismont et al, 2015) y su presencia ha sido predicha también en R. prolixus (Alzugaray et al, 2013). La expresión del mRNA se ha confirmado en órganos reproductores, en el SNC y en el complejo CC-CA y sistema digestivo, todos ellos órganos blanco de la acción del péptido (Verlinden et al, 2015).…”
Section: Receptores De Membrana Acoplados a Proteína G (Gprc)unclassified